Effect of physical factors on the amylase production from isolate M - Tharsini Santhiran (2024)
The demand for amylase enzymes has been increasing worldwide. Animals, plants and microbials are the several sources of amylase produce. In amylase enzyme production, the physical factors play crucial roles such as pH, temperature, agitation, incubation time and inoculum size. In this study, the physical factors mentioned are evaluated with different values. It aids in determining if the physical factors have the capability of producing high or have any effect on the production. There are two objectives for this study which are to find the best incubation time for the amylase production, to optimize the physical factors; pH, temperature, agitation, incubation time and inoculum size to obtain highest production rate of amylase and to apply the best physical factors; pH, temperature, agitation, incubation time and inoculum size toget highest production of amylase. The amylase producing bacteria were screened using iodine through starch hydrolysis test. Response Surface Methodology (RSM) as tool used in the study to optimize the best physical factors worked on the production of amylase enzyme. Five different independent variables were chosen to test the physical factors in this RSM. After conducting different incubation times, 24 hours was the optimum incubation time for the highest production of amylase compared to 48 hours and 72 hours. Among the other four physical factors, agitation and pH contribute to produce more production at 150 rpm and pH 7. Highest amylase activity was obtained among the experimental design 57.654 (U/mL). In short, the highest and lowest production was obtained from the same level of agitation and pH, but the effect was from inoculum size and temperature.